Estrategias de posicionamiento de Radio libre del cantón Babahoyo - Jumbo Cabrera, Maria Estefanya (2020)
The present case study was carried out on Radio Libre 93.9 FM, in the city of Babahoyo, the central theme of analysis is the positioning strategies that the company has applied in recent years. The objective is to identify the tactics used by this broadcaster to obtain a higher audience rate, which allows highlighting the positive aspects, as well as the weaknesses that it presents in its implementation, so that certain aspects related to continuous improvement can be suggested. The main problems detected in the design of positioning strategies are related to shortcomings in the basic functions of administrative processes, that is, it is not planned effectively, the organization lacks specificity, management does not always establish clear guidelines and the Control is not concurrent. To obtain the pertinent information, two research techniques have been used, the first is the interview directed to the radio director and the second has been conducted to the general public. The results have shown that Radio Libre 93.9 has reached an important position in the local market, however, there is a market share that has resistance to listen to the programming presented in it. The research paper concludes by stating that the communication company makes use of digital marketing, but requires more momentum in this regard to obtain more and better results.